John Henry Newman on the Nature of the Mind : Reason in Religion, Science, and the Humanities. - Rupert, Jane, 1943- (Lexington Books, 2011)
Jane Rupert shows how Catholic philosopher, theologian, and priest John Henry Newman sheds light on contemporary liberal education and the humanities by distinguishing between the different ways reason functions in science, religion, and in literature. Rupert discusses the range of Newman's thought on several fronts, including intellectual history, theories of knowing, the controversy between science and religion, the defense of the liberal arts and the aims of Catholic education.